Pentingnya Penerapan Manajemen Strategis di Rumah Sakit untuk menjadi Rumah Sakit Pilihan Masyarakat - Layli Rahmawati (Yayasan Pendidikan Medika Indonesia, 2022)
Hospital leaders are aware of various conditions that can reduce or enhance hospital development. Meanwhile, clinicians tend not to see the development of regional hospitals as important. Disagreements within the hospital eventually resulted in the hospital losing control over its development and decreasing competitiveness. Then, a phenomenon called the bulgurization of government hospitals emerged, only for the poor who had no choice and the government hospital subsidies were so small that they were unable to bind hospital staff to work full time. For this reason, strategic management is needed to get out of the above conditions. The method used in this paper is a literature review. The results of the research above are strategic management can be used to prevent government hospitals from falling as an inferior service institution. In essence, hospital strategic management is supported by a hospital strategic planning model, followed by proper implementation and control. The strategic planning model emphasizes the issue of vision and analysis of external and internal factors that can affect the achievement of institutional goals. These internal factors can show the strengths and weaknesses of the institution, while the analysis of external factors can describe the obstacles and encouragement from outside the institution.